Factors of external environment and their influence on activities of distilleries in Ukrain - Vitvytska, Daria; Nikitenko, Olga (My University, 2019)
An enterprise is an open system, the development of which depends on the external environment. In modern conditions, any organization should not only be accustomed to the external environment by adapting its internal structure and behavior on the market, but also actively forming external conditions of its activity, constantly exposing threats and potential opportunities in the external environment.
Keywords: market environment; external environment; internal environment; alcohol production; ринкове середовище; зовнішнє середовище; внутрішнє середовище; виробництво алкоголю; кафедра ділової іноземної мови та міжнародної комунікації